PERBANDINGAN KETENTUAN KEPEGAWAIAN INDONESIA ANTARA UNDANG-UNDANG NOMOR 8 TAHUN 1974 JUNCTO UNDANG-UNDANG NOMOR 43 TAHUN 1999 TENTANG POKOK-POKOK KEPEGAWAIAN DENGAN UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Joshua Evan Dwitya Pabisa; Muhammad Rullie Febian R; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
Law is required to always adapt to the times. In this case, employment law, especially in Indonesia, has undergone several changes to follow the dynamics of employment law regulations. Employment law does regulate specifically for civil servants and separates them from private employees. Rules related to employment law are contained in Law Number 5 of 2014 concerning State Civil Apparatus (UU ASN). However, long before the enactment of the Act, the legal basis used in the employment law was Law Number 8 of 1974 concerning the Principles of Employment. This study looks at the differences in the substance that is renewed by the government in the regulation of employment law in order to support more optimal public services. In his research, the author uses a descriptive normative legal research method. This study uses document or literature study techniques. The author then analyzed using qualitative analysis methodss.